Pulmonary Arterial Hypertension: Iron Matters - Ramakrishnan, Latha; Pedersen, Sofia L.; Toe, Quezia K.; Quinlan, Gregory J.; Wort, Stephen J. (Frontiers in Physiology, 2018)
The interplay between iron and oxygen is longstanding and central to all aerobic life. Tight regulation of these interactions including homeostatic regulation of iron utilisation ensures safe usage of this limited resource. However, when control is lost adverse events can ensue, which are known to contribute to an array of disease processes. Recently, associations between disrupted iron homeostasis and pulmonary artery hypertension (PAH) have been described with the suggestion that there is a contributory link with the disease process. This review seeks to highlight this literature and suggests the potential for therapeutic options to restore iron homeostatic balance in PAH.